T106. KARXT: A M1/M4 PREFERRING MUSCARINIC AGONIST FOR THE TREATMENT OF SCHIZOPHRENIA. (9th April 2019) - Brannan, Stephen; Miller, Andrew; Felder, Christian; Paul, Steven; Breier, Alan
Abstract: Background: Xanomeline is a M1 /M4 preferring muscarinic agonist that has demonstrated antipsychotic and pro-cognitive effects in both schizophrenia (Shekar, et al, 2008) and Alzheimer's disease (Bodick et al, 1997). However, its peripheral cholinergic side effects, including nausea, vomiting and diarrhea, have prevented its continued clinical development. A previous Phase I clinical trial demonstrated that the addition of trospium, a peripheral cholinergic receptor antagonist that does not cross the blood brain barrier, to xanomeline substantially improved its tolerability by reducing peripheral cholinergic side effects. We now report the results of a Phase 1, multi-dose safety study aimed at optimizing the combination of xanomeline with trospium (KarXT) using a new BID co-formulation. Methods: 69 healthy volunteers participated in the phase 1 multiple ascending dose (MAD) study of KarXT focusing on peripheral cholinergic side effects (nausea, vomiting, diarrhea, excess sweating and salivation), safety and tolerability. The study design was comprised of a 2-day titration period of either placebo or a KarXT dose of 50 mg xanomeline + 20 mg trospium followed by a 5-day treatment period. The doses (all BID) assessed were: xanomeline 100 mg, 125 mg and 150 mg in combination with trospium 20 mg or 40 mg. Results: The 2-day titration of 50/20 was well tolerated in all cohorts. Doses of 100 and 125 BID of xanomeline were also well tolerated when paired with 20 mg and 40 mg BID of trospium, respectively. Across the cohorts, cholinergic adverse events (ChAEs) were correlated with xanomeline dose. Increasing trospium dose ameliorated ChAEs, and lead to the observance of some anticholinergic adverse events (AEs). Some cohorts tested on 40 mg trospium BID reported signs of anticholinergic effects (i.e., dry mouth), particularly in the cohort receiving 125 mg BID of xanomeline. The total number of subjects reporting ChAEs in cohorts on xanomeline of 100 mg (39%) or 125 mg (33%) was similar to that seen in KAR-001, our previous phase 1 study (34%). Most ChAEs occurred within the first few days of starting or increasing the study drug. The majority of these AEs at 100 mg and 125 mg xanomeline-dose levels were mild and transient in nature. None of the cohorts showed meaningful changes in orthostatic HR or obvious differences in BP between placebo and KarXT compared to placebo. All cohorts receiving KarXT showed placebo-adjusted increases in mean resting HR consistent with past studies with xanomeline where short-term increases in resting HR were observed that normalized to baseline over time. Both trospium and xanomeline exposures (AUCs) and variability were comparable to KAR-001 where the compounds were given using separate formulations. Discussion: The new KarXT co-formulation of xanomeline and tropsium performed well in healthy subjects and is currently being tested in patients with schizophrenia. Longer terms studies will provide further data around the safety and tolerability of KarXT, as well as the possible attenuation of AEs over time. Importantly, the tolerability observed in this healthy volunteer study may not be representative of schizophrenic patients, who tolerate currently marketed antipsychotic medicine better than healthy volunteers. No new safety signals were reported in the present study. The timing and duration of AEs were related to peak drug levels (Cmax) and suggest that there is a potential for increased tolerability over time. In addition, all AEs rapidly returned to baseline levels upon dosing discontinuation. Consistent with our previous studies, KarXT is substantially better tolerated than xanomeline alone.